Long-Term Wastewater Surveillance for SARS-CoV-2: One-Year Study in Brazil - Martins, Renan Moura [UNESP]; Carvalho, Tamara [UNESP]; Bittar, Cintia [UNESP]; Quevedo, Daniela Muller; Miceli, Rafael Nava; Nogueira, Mauricio Lacerda; Ferreira, Helena Lage; Costa, Paulo Inácio [UNESP]; Araújo, João Pessoa [UNESP]; Spilki, Fernando Rosado; Rahal, Paula [UNESP]; Calmon, Marilia Freitas [UNESP] (MDPI, 2022)
Wastewater-based epidemiology (WBE) is a tool involving the analysis of wastewater for chemicals and pathogens at the community level. WBE has been shown to be an effective surveillance system for SARS-CoV-2, providing an early-warning-detection system for disease prevalence in the community via the detection of genetic materials in the wastewater. In numerous nation-states, studies have indicated the presence of SARS-CoV-2 in wastewater. Herein, we report the primary time-course monitoring of SARS-CoV-2 RNA in wastewater samples in São José do Rio Preto-SP/Brazil in order to explain the dynamics of the presence of SARS-CoV-2 RNA during one year of the SARS-CoV-2 pandemic and analyze possible relationships with other environmental parameters. We performed RNA quantification of SARS-CoV-2 by RT-qPCR using N1 and N2 targets. The proportion of positive samples for every target resulted in 100% and 96.6% for N1 and N2, respectively. A mean lag of -5 days is observed between the wastewater signal and the new SARS-CoV-2-positive cases reported. A correlation was found between the air and wastewater temperatures and therefore between the SARS-CoV-2 viral titers for N1 and N2 targets. We also observed a correlation between SARS-CoV-2 viral titers and media wastewater flow for the N1 target. In addition, we observed higher viral genome copies within the wastewater samples collected on non-rainy days for the N1 target. Thus, we propose that, based on our results, monitoring raw wastewater may be a broadly applicable strategy that might contribute to resolving the pressing problem of insufficient diagnostic testing; it may represent an inexpensive and early-warning method for future COVID-19 outbreaks, mainly in lower- and middle-income countries.
Keywords: epidemiology; qRT-PCR; SARS-CoV-2; wastewater